Papel y grillos, los jueces y el gobierno en Tucumán, 1820-1840. - Gabriela Tío Vallejo (Nuevo mundo - Mundos Nuevos, 2010)
In this article we propose to identify some features of the administration of justice between 1820 and 1840, when the provincial state is constituted in the context of the dissolution of the central power in the River Plate. In the first part, we describe the changes of the administration of justice after the extinction of the Cabildo, the difficulties caused by the absence of instances of appeal out of the province, the coexistence of legal regulations and the growth of the power of the governor. In the second part, these changes are observed from the analysis of the criminal processes originated in rural world. We analize the interaction between ordinary jurisdiction and territorial justice and we try to recognize across the attributions of the rural judges and his relations with military and police authorities, the possible links between justice and consolidation of provincial governor.